Morphohistological analysis of the reproductive system of Bostryx conspersus (Sowerby, 1833) (Gastrópoda, Bulimidae) from Pacta Lomes. Lima, Peru - López, Fela (1998)
Bostryx spp is one of the most conspicuous genus from the Bulimulidae; B. conspersus is considered a typical snail from the coastal lomes malacofaune. Our objective is to contribute to the morphohistologycal knowledge of the reproductive system in order to enrich the basic information of the reproduction of the specie and, that it can serve us in a short period as a pattern to compare others individuals of the same genus. Mature snails were processed, collected at the Pacta lomes, Department of Lima in July, 1994. The conquiological study was carried out in accord of Arrarte (1953). The specimens were dissected following the Beaumont & Cassier technique (1970). The procedure follows the histological protocol, obtaining serial samples between 6-8 m m; followed by the Haematoxilin-Eosin dyes. The gonadal complex of B. conspersus is described, specially the calcareal nodules of the albumen gland into the epitelials cells.